ESSAY ON UNIFIED EXPOSITION OF FOUR MAJOR THEOREMS IN TOPOLOGY - GARNADI, A. D. (School of Data Science, Mathematics and Informatics, IPB University, 2002)
This essay is an expository notes on four major theo- rems in Topology. The only prerequisites to comprehend this notes are basic knowledge in real analysis, elementary point set topology, and mathematical maturity.